The Effect of Promotion and Brand Image on PT Shaza's Product Purchase Decision: Case Study in South of Tangerang Area - Iis Noviyanti; Juwita Ramadani Fitria; Randhy Agusentoso (Journal of Research in Business, Economics, and Education, 2021)
The background of the problem in this research is about along with the progress of the times and science and technology, human food needs are also increasing rapidly. Various kinds of food products began to be varied with various shapes, colors, and tastes. Sales promotion is also synonymous with various interesting and entertaining activities. With enough food, the human food chain will be fulfilled properly. remembering that, food is a basic need that is very important for human survival. This study aims to determine the effect of promotion and brand image, either partially or simultaneously on purchasing decisions on PT SHAZA products (a case study in the South Tangerang area). In this study, data were collected through a questionnaire method using a Likert scale on 100 consumers with a simple random sampling technique using non-probability sampling analysis and parametric inferential statistics. The data analysis techniques used are: 1. Validity test, 2. Reliability test, 3. Classical assumption test, 4. Multiple linear regression test,5. Test the correlation coefficient 6. Test the coefficient of determination 7. Test the hypothesis partially and simultaneously. There is no significant effect between promotions on consumer purchasing decisions based on research results. There is a significant influence between the Brand Image variables on purchasing decisions based on the research that the author did and there is a simultaneous significant effect between promotion variables and Brand Image on consumer purchasing decisions based on research results.